(3cJGH aj GdLZQGajGs
(3ChdgG (B:s
(3TGeI LHd bQjH ef ecI s
(3BNQgG (B:s
(3GdHGH GdKGdK YTQ ai PcQ GdeSc hGdYfHQ hgd gh MTjT s
(3GdeDda ef GdbQf GdSGOSs
(3GdfSNI HgG MhGTs
(3GdfSNI eShOI GdeDdas
(3bWYI ef GdcJGH jJMOK ajg GdeDda Yf GHf YeQ GdebOSi s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdLZQGajG h GdHdOGfs